Ответы и объяснения

Лучший Ответ!
2012-04-22T06:02:49+00:00

(m²-5m+6) : (m²+7m+12)   *   (m²+3m): (m²-4m+4)     = 

                      m²+7m+12 = 0                      m²-4m+4 = 0

по т.Виета       m₁ + m₂ = -7               по т.Виета       m₁ + m₂ = 4

                        m₁*m₂ = 12                                      m₁*m₂ = 4

                          m₁ = -3                                                 m₁ = 2

                          m₂ = -4                                                 m₂ = 2


=  (m - 2)(m- 3) m (m+3)   /   (m + 3)(m + 4)(m - 2)(m- 2) =

=  (m- 3) m  /  (m + 4)(m - 2)